How the brain memorizes the world from others’ perspectives: investigating allocentric encoding of object features during perspective taking - Nanbo Wang; Shuo Huang; Junyang Cai; Ruiyi Huang; Haiyan Geng (BMC Psychology)
Abstract Background Individuals are frequently encouraged to consider others’ perspectives to enhance social interactions. To achieve this objective, understanding others’ visual world is significantly beneficial. However, as a fundamental aspect of human cognition, to what extent can individuals effectively memorize object information when adopting another’s viewpoint? Can all features about the object be exclusively memorized in an allocentric manner or only some of them? The present study aims to investigate this issue. Methods We designed a novel paradigm by integrating a change-detection paradigm with a perspective taking task to investigate these questions. A total of 226 undergraduates were recruited in four behavioral experiments. Participants were instructed to memorize the target dimension features of a memory array from an avatar’s perspective while ignoring irrelevant dimension features. We assessed the impact of irrelevant feature changes on individuals’ identification of memorized target features to determine whether irrelevant features are automatically memorized in an allocentric manner. Results We found that individuals engaged in other-perspective processing can adopt either object-based encoding, where irrelevant features are automatically encoded into memory in an allocentric manner along with the target feature, or feature-based encoding, where irrelevant features will not be memorized without controlled intention. The selection of encoding mechanism depends on the discriminability of task-irrelevant dimensions. Object-based encoding is employed when the irrelevant dimension exhibits high discriminability while feature-based encoding is utilized when it demonstrates low discriminability. Moreover, these mechanisms are specific to embodied processing, and alternative strategies like object-rotation will lead to different encoding rules. Conclusions Overall, this study revealed that individuals follow a “coarse-to-fine” principle of memorizing object features when adopting others’ perspectives and suggests the existence of allocentric memorization of irrelevant information during perspective taking.